The focus of public discourse on child abuse in kindergartens: analysis of articles on child abuse in newspapers of China from 2010 to 2017 - Baoan Feng; Xingping Zhou (Problemy Wczesnej Edukacji)
As a social phenomenon, child abuse in kindergartens is not only an educational but also a legal issue. This study analyzed 423 critical articles on child abuse in kindergartens published by 103 newspapers in China from 2010 to 2017. The results of the research are as follows: (1) The change of public opinion on child abuse conforms to the law of public opinion development in the latent period, outbreak period, spread period, repetition period, remission period and long tail period of the dissemination of hot topics of public opinion; (2) The range of social groups concerned about child abuse has been expanding year by year, until 2017, a total of 22 categories of social groups have paid attention to child abuse; (3) The focus of public attention on the child abuse incidents includes 23 aspects, such as the supervision responsibility, harm, punishment, system, prevent, treatment and morality. Among them, it mainly focuses on supervision and rule of law, and lacks humanistic care for preschool teachers.